2021
DOI: 10.1017/ipm.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Spanish version of the Fear of COVID-19 scale in Paraguayan population

Abstract: Objective: The aim of this study is to test the psychometric properties of the Spanish validation of the Fear of COVID-19 Scale (FCV-19S) in Paraguayan population. Methods: Participants were recruited through an Internet-based survey. All participants whose scores in the Hospital Anxiety and Depression Scale (HADS) and The Fear Questionnaire (FQ) were greater than zero were included. 1245 subjects responded voluntarily: 1077 subjects, scoring >0, were considered. Results:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
3
24
0
4
Order By: Relevance
“…Since its development, the Fear of COVID-19 Scale has been translated and adapted to several languages [ 13 , 14 , 31 50 ]. The initial study examined the validity against the Hospital Anxiety and Depression Scale and Perceived Vulnerability to Disease Scale [ 30 ], similarly to the Portuguese [ 5 ], English [ 31 ], Italian [ 13 ], Arabic [ 46 ], Spanish [ 44 ] and Japanese [ 37 ] adaptations, while other studies confirmed the validity using various other measures of depression and anxiety [ 14 , 32 35 , 38 , 39 , 42 , 43 , 45 , 47 , 49 , 50 ]. The Fear of COVID-19 Scale has high reliability across translations and cultural adaptations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its development, the Fear of COVID-19 Scale has been translated and adapted to several languages [ 13 , 14 , 31 50 ]. The initial study examined the validity against the Hospital Anxiety and Depression Scale and Perceived Vulnerability to Disease Scale [ 30 ], similarly to the Portuguese [ 5 ], English [ 31 ], Italian [ 13 ], Arabic [ 46 ], Spanish [ 44 ] and Japanese [ 37 ] adaptations, while other studies confirmed the validity using various other measures of depression and anxiety [ 14 , 32 35 , 38 , 39 , 42 , 43 , 45 , 47 , 49 , 50 ]. The Fear of COVID-19 Scale has high reliability across translations and cultural adaptations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is debate whether the Fear of COVID-19 Scale has a stable single-factor structure [ 4 ] as reported in the initial study [ 30 ] and several adaptations [ 5 , 13 , 14 , 31 , 32 , 34 , 36 , 38 43 , 46 , 50 53 ] or if it is bi-factorial as reported in Paraguayan [ 44 ], Israeli [ 45 ], Chinese [ 47 ], Norwegian [ 49 ], Argentinian [ 33 ], Peruvian [ 35 ], Japanese [ 37 ] and Eastern European [ 54 ] populations. The two-factor models define a cognitive and somatic fear [ 49 ] or emotional and psychological [ 37 ] fear.…”
Section: Introductionmentioning
confidence: 99%
“…Paraguayan population has coped with the dissemination of misleading information and false news even before the virus entered the country (March 2020), which generated a rapid collective reaction of neurosis with compulsive food-shopping, xenophobia, risky health care practices ( Moreno Fleitas, 2020 ), fear ( Barrios et al, 2021 ), and stress ( Torales, Ríos-González, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…fear), preferably the item numbers should be balanced related to each dimension, particularly when more than one latent factor may be present. Compared to the huge number of construct dimensionality evaluation by one-factor CFA, only few completed two-factor CFA, even fewer reported the results of EFA (5,6,8,19).…”
Section: Introductionmentioning
confidence: 99%